2012
DOI: 10.1111/mmi.12105
|View full text |Cite
|
Sign up to set email alerts
|

Nus transcription elongation factors and RNase III modulate small ribosome subunit biogenesis in Escherichia coli

Abstract: Summary E. coli NusA and NusB proteins bind specific sites, such as those in the leader and spacer sequences that flank the 16S region of the ribosomal RNA transcript, forming a complex with RNA polymerase that suppresses Rho-dependent transcription termination. Although antitermination has long been the accepted role for Nus factors in rRNA synthesis, we propose that another major role for the Nus modified transcription complex in rrn operons is as an RNA chaperone insuring coordination of 16S rRNA folding an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 78 publications
6
53
0
Order By: Relevance
“…NusE, which is now known to be ribosomal small subunit protein S10, binds NusG and as such is thought to be involved in ensuring that a ribosome closely follows the transcribing RNA polymerase, thus coupling translation to transcription (Burmann et al , 2010; McGary and Nudler, 2013). In addition, NusA interacts with translesion DNA polymerases to affect DNA repair (Cohen et al , 2009), and with NusB it may even be involved in intracellular RNA folding and processing (Bubunenko et al , 2013). Thus, these early lambda-host interaction genetic studies revealed previously unsuspected complexities of transcription and led directly to the discovery and characterization of factors that control RNA polymerase elongation and termination.…”
Section: Historical Importance and Recent Progressmentioning
confidence: 99%
“…NusE, which is now known to be ribosomal small subunit protein S10, binds NusG and as such is thought to be involved in ensuring that a ribosome closely follows the transcribing RNA polymerase, thus coupling translation to transcription (Burmann et al , 2010; McGary and Nudler, 2013). In addition, NusA interacts with translesion DNA polymerases to affect DNA repair (Cohen et al , 2009), and with NusB it may even be involved in intracellular RNA folding and processing (Bubunenko et al , 2013). Thus, these early lambda-host interaction genetic studies revealed previously unsuspected complexities of transcription and led directly to the discovery and characterization of factors that control RNA polymerase elongation and termination.…”
Section: Historical Importance and Recent Progressmentioning
confidence: 99%
“…The examples of on/off regulation at the transcript elongation stage, such as promoter-proximal pauses in metazoans (Adelman and Lis, 2012) and antitermination in prokaryotes (Santangelo and Artsimovitch, 2011), are also known. In other cases, transcription elongation control is mediated by coupling of transcription to downstream processes, such as RNA translation, processing, and folding (Proshkin et al, 2010; Bubunenko et al, 2013). The multisubunit RNAPs evolved to elongate relatively inefficiently in the absence of proper coupling, thereby enabling the downstream processes to control the elongation rate.…”
Section: Introductionmentioning
confidence: 99%
“…Both NusA and NusB are important for rRNA synthesis and ribosome biogenesis (Bubunenko et al, 2013). Only NusA binds to RNA Pol in vitro .…”
Section: Rna Pol Foci Are Transcription Factories For Rrna Synthesis mentioning
confidence: 99%